2021
DOI: 10.1029/2020ja028670
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Coalescence of Magnetopause Flux Ropes and Their Dependence on IMF Clock Angle: Three‐Dimensional Global Hybrid Simulations

Abstract: Flux ropes are ubiquitous at Earth's magnetopause and play important roles in energy transport between the solar wind and Earth's magnetosphere. In this study, structure and coalescence of the magnetopause flux ropes formed by multiple X line reconnection in cases with different southward interplanetary magnetic field (IMF) clock angles are investigated by using three‐dimensional global hybrid simulations. As the IMF clock angle decreases from 180°, the axial direction of the flux ropes becomes tilted relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Note that Case 1 in this paper is the same as Case 3 in Guo et al (2021), in which the FR coalescence has been well identified. Moreover, the simulation domain of Case 1 contains a small dayside cusp region, and it is not enough to simulate the re-reconnection between FR and the cusp field lines.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Note that Case 1 in this paper is the same as Case 3 in Guo et al (2021), in which the FR coalescence has been well identified. Moreover, the simulation domain of Case 1 contains a small dayside cusp region, and it is not enough to simulate the re-reconnection between FR and the cusp field lines.…”
mentioning
confidence: 84%
“…Using 3‐D global hybrid simulations, Guo et al. (2021) studied the 3‐D structures and evolution of FRs formed by magnetopause reconnection with different southward IMF clock angles, and they found that whether and where FR coalescence occurs are controlled by the IMF clock angle. However, the detailed coalescence process, that is, the topological change of magnetic field lines during the re‐reconnection, is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, J. Guo et al. (2021a, 2021b) used a 3‐D global hybrid simulation to show that when the IMF is southward, the number of flux ropes is 4–8, the length of flux ropes can be up to 12 RE and the diameter of the flux ropes can be up to 2 RE. However, in this study, we find that when the IMF is northward, the number of flux ropes is 1–2, the length of flux ropes is only about 3 RE and the diameter of the flux ropes is less than 1 RE.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Magnetopause reconnection can form flux transfer events (FTEs; Russell & Elphic, 1978), which is an effective mechanism for energy transport in the solar wind‐magnetosphere coupling. FTEs are usually interpreted as magnetopause flux ropes with helical magnetic field lines formed by multiple X‐line reconnection (Z. F. Guo et al., 2020; J. Guo et al., 2021a; Hasegawa et al., 2010; Lee & Fu, 1985; Øieroset et al., 2016; Tan et al., 2011; Wang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%